P651 Disease severity and intensity of therapy predicts serious adverse events in paediatric ulcerative colitis: the DEVELOP experience. (25th January 2019) - Winter, H; Izanec, J; Busse, C; Wang, Y; Hyams, J
Abstract: Background: DEVELOP is a multi-centre (USA, Canada, European Union), prospective, observational registry of the long-term safety and clinical status of 6070 paediatric patients with inflammatory bowel disease (IBD including 1678 ulcerative colitis [UC] patients) treated with anti-tumour necrosis factor biologics (aTNF) and/or other medical therapies as part of physician dictated clinical care. AIM: To identify covariates that were significant predictors to time to first serious adverse event (SAE) in patients with UC. A SAE is defined as any undesirable experience that results in hospitalisation, requires medical intervention or is otherwise life-threatening. Methods: Physicians participating in the registry prescribe IBD treatments based on their usual clinical practice and standards of care. Patients are categorised into cohorts according to their IBD medication exposure. The cohorts represent prevalent or incident exposure, including patients receiving therapy prior to enrolment and patients receiving therapy during registry follow-up. Enrolment was targeted such that about 50% of the initial population had been exposed to originator infliximab. Hazard ratio (HR) for SAE was calculated by stepwise Cox regression modelling. Results: Time to first SAE are shown in Table 1. This includes 1121 UC patients who were exposed to aTNFs as the only biologic and/or non-biologics and had at least 1 post-baseline follow-up visit, complete baseline covariate data, and complete disease severity data (partial Mayo score) at event or censoring. The covariates that were significantly associated with a shorter duration of time to first SAE in UC patients included combination therapy with aTNF/immunomodulators (IMM) and corticosteroids (CS) or combination therapy with aTNF and CS. Monotherapy with CS, disease activity (hazard ratio [HR] 2.657) and recent hospitalisation were also significantly associated. Conversely, combination therapy with aTF and IMM or monotherapy with aTNF or IMM alone were not associated with significantly increased risk of time to first SAE. Conclusions: In terms of HR, disease severity was the strongest predictor of time to first SAE. Combination therapy with aTNF and CS and also triple therapy with aTNF, CS and IMM were predictors as was monotherapy with CS. On the other hand, monotherapy with aTNF or with IMM were not found to be significant predictors.